Participatory Based Transactions in Sharī‘ah (Islamic Commercial Law) and their Role in the Development of Rural Local Agricultural Sector in Khyber Pakhtunkhwa (Sharī‘ah Based Newly Proposed Models) - Lutf Ullah; Zia ul Haq (Journal of Islamic and Religious Studies, 2018)
Local farming is, indeed, the most important sector of agriculture through which farmers grow food. However, owing to their weak financial conditions, they are not able to get maximum benefits from their labours for most of the times. The case of Pakistani farmers, particularly in rural areas of KP (Khyber Pakhtunkhwa), is not different in this connection. They frequently resort to formal and informal sources of financing to accomplish their basic agricultural requirements: both crops and non-crops inclusive. However, all these sources advance financing facility on interest basis. Being typical Muslims, such agricultural credit is, therefore, avoided by these farmers and, as a result, they always endure on their financial grounds. In such situations, some substitute arrangements are recommended to reciprocate with their problems. This alternative is offered by Sharī‘ah through various commercial transactions – among which participatory based transaction i.e. Mushārakah is the most suitable and important one. In the present work, various models are proposed on the basis of such transaction to fulfill various agricultural requirements of farmers, living in rural areas of KP. In addition, such models are structured in the light of basic theory, available in the classical literature of Islamic law, in order to make them more Sharī‘ah based rather Sharī‘ah compliant. The proposed models are then, at the second stage, tested at ground level to strengthen further their viability for all stake holders. Findings show that all agricultural requirements, particularly heavy machinery and transport, can be realized through such models provided if they are applied in their true spirit. Moreover, content analysis and focused group technique of qualitative research have been used, as a research methodology, for the investigation of the issue in the present work.